A reappraisal of the lost suids from the Late Miocene of Gravitelli (Sicily, Italy) and paleobiogeographical implications - Iannucci, Alessio (Palaeoworld, 2024)
The long-lost mammal fauna from Gravitelli (Messina, Sicily, Italy) represents one of the most important records for investigating faunal dynamics during the Late Miocene of the Mediterranean, although it is unfortunately only known from descriptions carried out in the early 1900s, as the original collection was lost during the Messina Earthquake of 1908. Gravitelli suids have been referred to Propotamochoerus sp. after the redescription of the casts of two specimens that survived to the present day. However, there is further material that has not been considered, which makes that of Gravitelli one of the most abundant samples of Late Miocene suids from Italy, with a minimum number of four individuals represented. A reappraisal of all Gravitelli suids allows to ascribe them to Propotamochoerus provincialis (Suinae, Dicoryphochoerini), following a comparison with related Late Miocene to Pliocene species from Eurasia. Moreover, the re-examination of the geological setting of the locality reveals that the mammal fauna of Gravitelli occurred well below the pre-evaporitic deposits of the Tripoli Formation, whose base is dated in Sicily at ∼7 Ma. Therefore, Gravitelli fauna either dates to the late Tortonian or, at most, to the earliest pre-evaporitic Messinian, corresponding to MN 11 or MN 12 in terms of mammal biochronology. This implies that the occurrence of P. provincialis at Gravitelli is the earliest in Italy and that emerged land masses connected Sicily with the European mainland earlier than 7 Ma. Available dates support a diachronous dispersal of Propotamochoerus in western Europe during the Turolian, being first known from the Balkans ∼8.3 Ma, then from Gravitelli prior to 7 Ma, and then from the Iberian Peninsula since ∼6.2 Ma. A similar pattern is known for Mesopithecus (Cercopithecidae). Although often discussed in light of its potential significance for Afro-Eurasian dispersals, only a fraction of the mammal fauna of Gravitelli has been reconsidered systematically. Notwithstanding the necessity of such dedicated studies, the faunal elements identified so far have an almost entirely European character and no species is shared with Cessaniti (Calabria), despite the two faunas have often been considered part of a paleobioprovince documenting a connection between southern Italy and northern Africa. At Gravitelli, the only species of African origin is the endemic hippo Hexaprotodon? siculus, but the extensive fossil record of insular hippopotamids testifies to their ability to colonize islands even in the absence of land bridges. Gravitelli hippos are nonetheless noteworthy, as the revised age of the site implies that they represent the earliest hippopotamids known outside Africa.